Non-Linear Instability of Pin-Ended Functionally Graded Material Arches Under Locally Distributed Radial Loads - Zhou, Jinman; Li, Guangjun; Lu, Hanwen; Chen, Zhou; Pan, Zhenyu; Zhu, Jian (Frontiers in Materials, 2022)
An arch is a common structure in bridge engineering, which often suffer from stability problems. In this paper, in-plane nonlinear instability of pin-ended functionally graded materials (FGMs) arches with two cross-sectional types under local radial loads is studied. New analytical solutions of nonlinear equilibrium path, limit point instability, bifurcation instability and multiple limit point instability of pin-ended FGMs arches under local radial load are obtained. Modified slenderness corresponding to different instability patterns of FGMs arches are also derived. Compared with the numerical results of ANSYS demonstrate that the analytical solution is accurate. The results show that cross-sectional types of the FGMs arches has a great influence to the limit point instability and the bifurcation instability. Localized parameters increase lead to limit point instability load and bifurcation instability load increases, while the increase of modified slenderness ratio results in the decrease of limit point instability load and bifurcation instability load. In addition, material proportion coefficient and power law index increase can also lead to limit point instability load and bifurcation instability load decrease.